2020
DOI: 10.3390/s20216332
|View full text |Cite
|
Sign up to set email alerts
|

A Single-Fed Multiband Antenna for WLAN and 5G Applications

Abstract: In this paper, a slotted conical patch connected to a small triangular patch multiband antenna for both microwave and millimeter-wave applications is presented. The designed antenna has three characteristics. The proposed antenna is a multiband, having a compact size of 0.35λ0 × 0.35λ0 × 0.004λ0 at its lowest operational frequency, i.e., 2.4 GHz, and more importantly, it can cover both the microwave and millimeter-wave bands with a single feeding. According to the −10 dB matching bandwidth, experimental result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…In Ref. [ 14 ], a multiband antenna for microwave and millimeter-wave applications is presented. The proposed antenna consists of a slotted, conical patch connected to a small triangular patch.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…In Ref. [ 14 ], a multiband antenna for microwave and millimeter-wave applications is presented. The proposed antenna consists of a slotted, conical patch connected to a small triangular patch.…”
Section: Summary Of the Special Issuementioning
confidence: 99%
“…If the electromagnetic sensors are narrowband, i.e., approximately 100 MHz and we want to analyze a Cherenkov radiation in a band of 100 MHz ÷ 1 GHz is required, then n sb = 9; so, we will obtain N = 288,000 electromagnetic sensors and a number of (n x × n y ) = 400 holes in the salt block. It is observed that a more economical option would consist in the use of the electromagnetic wide-band sensors [26].…”
Section: Description Of the Problemmentioning
confidence: 99%
“…This configuration can support six resonating bands at resonant frequencies of 2.88 GHz, 3.64 GHz, 3.95 GHz, 4.38 GHz, 4.81 GHz, and 5.6 GHz with five rejection bands between them where two of these rejection bands have a reflection coefficient level larger than 5 dB. Four spectrums for sub-6 GHz and mm-wave applications that have been radiated from a slotted patch of conical shape connected to a small triangular patch were proposed in [20]; the design resonant frequencies were 2.4 GHz, 5.2 GHz, 5.8 GHz, and 27.5 GHz. An antenna element of the 'F' shape placed above a truncated ground plane has been proposed in [21] to operate in four reconfigurable frequency modes.…”
Section: Introductionmentioning
confidence: 99%